Successful treatment of recurrent refractory Kaposi’s sarcoma in AIDS: a case report - Li, Feng; Zheng, Rongrong; Yan, Jun; Zhang, Zhongdong; Liu, Hong; Shi, Jinchuan (Frontiers in Oncology, 2024)
Kaposi’s sarcoma (KS) is a soft tissue lesion that resembles a hyperpigmented angiosarcoma and is typically associated with human herpesvirus 8 (HHV-8) infection. It is most frequently observed in immunocompromised patients, particularly those with AIDS, and is also referred to as HIV-associated Kaposi’s sarcoma (AIDS-KS). The disease progresses rapidly, is challenging to manage, and has a high mortality rate. This case report presents a patient with AIDS-KS who experienced relapse after chemotherapy with anthracyclines. Subsequent chemotherapy with the same method had no significant effect. However, complete remission was achieved after the addition of a programmed cell death protein 1(PD-1) inhibitor, as confirmed by pathological biopsy. The PD-1 inhibitor was well-tolerated and had few adverse effects. It also helped to improve the immune reconstitution of the patient. The report highlights the remarkable efficacy of the PD-1 inhibitor in treating AIDS-KS. This provides case support for PD-1 inhibitors for AIDS-KS.